Phosphate Release from Slow Release fertilizer using a mixture of Chitosan and Potato Flour as a coating (Universitas Negeri Semarang, 2019)
Indonesia has a high fertilizer demand because its use is easily dissolved during watering, so the fertilization process is inefficient. On the other hand, crab shells accumulate every year because the waste is almost 50% of the initial weight. One way to overcome this problem is to make a modified fertilizer into a slow release fertilizer by adding a bio-gel layer from chitosan and potato flour. The hydrophobic properties of chitosan and potato powder were chosen in addition to the amylopectin content of potato flour more than other types of starch. Then chitosan was dissolved using acetic acid, while potato starch was dissolved by distilled water by heating 76oC. Both mixtures are added to the fertilizer then stirred until the compost is coated. Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) were used to characterize the morphology and composition of the products. Addition of thickness to the outer layer of manure reached 35.56 Âµm. The O-H function group is found in the spectrum of potassium and phosphorus which shows that there is a hydrogen bond in chitosan and potato flour. The most substantial swelling is obtained at the K (chitosan): P (potato flour) ratio of 3:7. The wet retention test showed that the addition of chitosan and potato flour was able to withstand soil retention. In the release test for Phosphorus shows good results at a value of 0.923 mg/L.